Integration of Problem Based Learning and Scaffolding for Educational Purpose: A review - Girei, Mohammed Musa; Abdullah, Zaleha (International Journal of Psychosocial Rehabilitation, 2020)
Problem-based learning (PBL) is a student-centered approach that has potential to foster independent study and critical thinking skills. This review discusses how PBL incorporates scaffolding that could benefit vocational learning in Education. These are strategies employed to expose students to real-world problem solving, critical thinking skills and effective knowledge transfer through active engagement. This review employed a systematic approach. Eleven (11) research articles were selected and scrutinized. Results indicated that undertaking the role of a specialist as instructor can take a dynamic task in PBL strategy. Provide the necessary resources to build learners who could address ill-structured problems. Be able to use the application of real-life experience and specialist-level strategies to address the cognitive task. This complex skill cannot be acquired through conventional teaching. However, can be acquired through the scaffolding of progressive, stimulating learning opportunities, routine exercise and self-reflection. Solving real-world problems entails active collaboration and exploiting the potentials of technologies available for us. Thus, instructors need to be contented as facilitators of a learning situation that is often complex and challenging task. Consequently, it is established that the PBL and scaffolding have the potentials to enhance students’ critical thinking skills. Though, with a careful structure of authentic learning situation. The application of appropriate technology to offer an on-line scaffolding strategy can support student’s engagement with the learning activities. Though, if question prompts in PBL is provided in a complicated or difficult manner, the question prompts could be an interruption of learning instead of assistance.